Analysis of trapping sites for deuterium in W–Cr–Y SMART alloy. (May 2022) - Harutyunyan, Z.; Gasparyan, Yu.; Efimov, V.; Litnovsky, A.; Klein, F.; Pisarev, A.; Coenen, J.W.; Linsmeier, Ch.
Abstract: Deuterium (D) retention in tungsten-chromium-yttrium (W–Cr–Y) alloy depending on the irradiation fluence of 10 19 –5 × 10 21 D/m 2 at various sample temperatures in the range of 300–900 K was investigated using in-situ thermal desorption spectroscopy (TDS). The irradiation was carried out using 2 keV D3 + ions (670eV/D). An increased D retention compared to that of pure polycrystalline W and additional high-temperature peaks were observed in TDS. The de-trapping energy of 2.21 ± 0.05 eV for these traps was determined by the Kissinger method using the series of experiment with different heating rates. The total D retention dropped down at elevated irradiation temperatures and was rather small at 900 K, but has a local maximum at about 700 K. Highlights: The D retention in the W–Cr–Y alloy irradiated by 2 keV D3 + ions was investigated. In-situ thermal desorption spectroscopy was performed at different heating rates. An additional temperature peak with the maximum at about 960 K was detected. The de-trapping energy of 2.21 ± 0.05 eV for high-energy traps was determined.